Feast : food of the Islamic world - Helou, Anissa, 1952- (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2018)
Award-winning chef Anissa Helou, an authority on the cooking of North Africa, the Mediterranean, and the Middle East, shares time-tested recipes, history, and stories from cuisines throughout the Muslim world. Born in Lebanon to a Lebanese mother and Syrian father, Helou has lived and traveled widely in this region, from Egypt to India, Indonesia to Pakistan, Qatar to Morocco, gathering an enormous variety of dishes associated with Arab, Persian, Mughal (or South Asian), and North African cooking.
Bread -- The whole beast -- Rice, grains, pasta & legumes -- The sea -- Spices, spice mixtures & spice pastes -- Fresh produce -- A sweet tooth.
Includes index.
Keywords: Cooking -- Islamic countries; Islamic cooking; Cooking, Middle Eastern; Cooking, North African; Cooking, Indic; Nonfiction; Cookbooks; Cookbooks